We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
489
2
avatar

a(2+4) + a(6-1) =

 Aug 9, 2015

Best Answer 

 #2
avatar+102466 
+5

a(2+4) + a(6-1) =

6a+5a=11a

 Aug 9, 2015
 #1
avatar+1222 
0

$${a}{\left({\mathtt{2}}{\mathtt{\,\small\textbf+\,}}{\mathtt{4}}\right)}{\mathtt{\,\small\textbf+\,}}{a}{\left({\mathtt{6}}{\mathtt{\,-\,}}{\mathtt{1}}\right)} = ABC{\mathtt{\,\small\textbf+\,}}ABC$$

.
 Aug 9, 2015
 #2
avatar+102466 
+5
Best Answer

a(2+4) + a(6-1) =

6a+5a=11a

Melody Aug 9, 2015

22 Online Users

avatar
avatar
avatar